2020
DOI: 10.3389/fmicb.2020.01835
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gut Microbiome and Short-Chain Fatty Acids (SCFAs) on Finishing Weight of Meat Rabbits

Abstract: Understanding how the gut microbiome and short-chain fatty acids (SCFAs) affect finishing weight is beneficial to improve meat production in the meat rabbit industry. In this study, we identified 15 OTUs and 23 microbial species associated with finishing weight using 16S rRNA gene and metagenomic sequencing analysis, respectively. Among these, butyrate-producing bacteria of the family Ruminococcaceae were positively associated with finishing weight, whereas the microbial taxa related to intestinal damage and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 87 publications
4
33
0
Order By: Relevance
“…Due to SCFAs widely participate in physiological and pathophysiological interactions between the gut microbiota and the host [35], we hypothesized that these breed-associated SCFAsproducing species should play a central role in the health, development, and growth of rabbits, and could be considered as potential biomarkers for production performance improvement [36]. Indeed, previous studies have demonstrated that Coprococcus, Ruminococcus, and Lachnospiraceae species are intimately correlated with growth performance of meat rabbits [18,37].…”
Section: Discussionmentioning
confidence: 99%
“…Due to SCFAs widely participate in physiological and pathophysiological interactions between the gut microbiota and the host [35], we hypothesized that these breed-associated SCFAsproducing species should play a central role in the health, development, and growth of rabbits, and could be considered as potential biomarkers for production performance improvement [36]. Indeed, previous studies have demonstrated that Coprococcus, Ruminococcus, and Lachnospiraceae species are intimately correlated with growth performance of meat rabbits [18,37].…”
Section: Discussionmentioning
confidence: 99%
“…Omega-3 PUFAs exert a positive effect through restoring the microbiota composition in individuals with various diseases and increasing the production of anti-inflammatory compounds, such as SCFAs [ 39 ]. Butyric acid-producing bacteria play an important role in maintaining human gut health by degrading nonfermentable dietary fibers into SCFAs, such as butyrate [ 40 ]. Butyrate is considered an essential energy source for the colonic mucosa that controls gene expression, inflammation, differentiation, and apoptosis in host cells [ 41 ].…”
Section: Omega-3 Pufas and The Gut Microbiotamentioning
confidence: 99%
“…Given that caecum is the primary site of fermentation, a large portion of studies on the microbiome of the digestive system of rabbit focused on the caecal and fecal bacterial communities [ 9 , 10 , 11 , 12 , 13 , 14 ]. The preliminary studies were animated to characterize the microbial population of caecum in order to understand its role in the digestive activity and health status of the rabbit [ 9 , 15 , 16 , 17 ]. Other studies investigated the bacterial communities that are involved in the improvement of health, welfare, and meat production of rabbits [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, better knowledge and a complete microbial mapping of all different parts of the gastrointestinal tract are necessary for promoting the health and welfare of the rabbit, whose market is going through a period of difficulty and it is the subject of animal welfare issues [ 24 , 25 ]. Indeed, new strategies could be developed to favor the establishment of an advisable and “healthy” intestinal bacterial community that increases the digestible efficacy of the nutrient and, at the same time, saves energy for the host [ 17 , 26 , 27 , 28 ]. Moreover, the development of a beneficial bacterial population can promote the maturation and functioning of the immune system and, as a consequence, could reduce the incidence of infectious diseases, with beneficial effects on the health and welfare of animals.…”
Section: Introductionmentioning
confidence: 99%